Sea surface temperatures from the Western Pacific Warm Pool across the last 17kyrs - Moffa-Sanchez, Paola; Rosenthal, Yair; Babila, Tali L; Mohtadi, Mahyar; Zhang, Xu (Supplement to: Moffa-Sanchez, P et al. (2019): Temperature Evolution of the Indo-Pacific Warm Pool Over the Holocene and the Last Deglaciation. Paleoceanography and Paleoclimatology, 34(7), 1107-1123, https://doi.org/10.1029/2018PA003455, 2019)
The Indo-Pacific Warm Pool (IPWP) contains the warmest surface ocean waters on our planet. Changes in the extent and position of the IPWP likely impacted the tropical and global climate in the past. To put recent ocean changes into a longer temporal context, we present new paleoceanographic sea surface temperature reconstructions from off Papua New Guinea (RR1313-23PC: 4.4939°S, 145.6703°E, 712 m water depth) which is at the heart of the Western Pacific Warm Pool (WPWP), which is the warmest region within the IPWP, across the last 17,000 years. A new surface temperature dataset from the northeast South China Sea is also presented (ODP1144: 20.053°N, 117.4189°E; water depth 2037 m). In both locations we use Mg/Ca measurements on G.ruber s.s. (white) to calculate sea surface temperatures.
Keywords: G.ruber; Holocene; Mg/Ca; Western Pacific